Decentralization and Town Development - Atnafu, Aldo Morka (International Journal of Social Sciences and Management, 2016)
Decentralized governance offers opportunities for achieving development through good governance and community participation at grass root (Ayenew, 2007).Thus, this study examines the contribution of decentralization for town development and; the opportunities and challenges of wereda decentralization for town development. The study was conducted in two selected Wereda capital towns in Metekel zone, Bulen and GilgelBeles. Data were collected from primary sources with the help of questionnaires, interviews and observation. The primary data were also supported by secondary documents such as federal and regional constitutions, proclamations, regulations, local development plans, official performance reports, and magazines. The data was analyzed qualitatively and quantitatively. The study revealed that wereda level decentralization actually has influenced development at grass root level in Metekel zone in general, and towns in particular. Better infrastructural provisions (education and health) were witnessed in the towns. This is due to better community participation in decision making process and availability of opportunity to express their interest. Though, more is expected, the financial capacity of towns has also registered progress. However, the situation in urban land delivery does not show an improvement. Partiality, bias, and unaccountability are major hindrances in urban land delivery. The top down hierarchy between town administrations and wereda administrators has become a major challenge for a full exploitation of town resource and administration. Besides, shortage of qualified manpower and weak community participation in development activities were also other factors that have impacted the further performance of towns. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 78-80